(untitled) (African Journal of Biomedical Research, 2023)
The relationship between exercise and renal function is a rather controversial topic. This study is aimed at investigating the overall effect of exercise as a preventive as well treatment option in the management of cisplatin-induced acute kidney injury (AKI). 25 male albino Wistar rats were acclimatized for two weeks then randomly divided into five groups (n=5): Group 1 (Control), Group 2 (Exercise group), Group 3 (cisplatin-induced), Group 4 (cisplatin +Exercise), Group 5 (Exercise+cisplatin). The animals in group 3, 4 and 5 were induced with AKI using intraperitoneal administration 3.0mg/kg Cisplatin which was administered for 3 days with a daily interval between each dose. The rats in group 2, 4 and 5 were subjected to aerobic exercise as a moderate regular exercise on a treadmill machine at the speed of 3km/h for 5 minutes at 0% inclination for 5 days/week for 3 week. After which the rats were sacrificed and blood, urine and kidney samples were obtained for laboratory analysis. Urine and serum electrolyte, creatinine and urea concentrations as well as urine albumin and serum cystatin C (Cys-C) concentration were analyzed. The finding of this study indicates that exercise when used as a treatment measure for cisplatin-induced AKI produced a mild functional and structural improvement. However, exercise as a preventive measure demonstrated a stronger tolerance to the toxicity ofcisplatin structurally but not functionally. This study also showed cys-C was a poor biomarker for the detection of AKI in rat subjects